When Long-Term Talent Commitments Become Consequential: Employee Engagement and Workplace Resilience Under Uncertainty - Eri Marlapa; Joko Sugiharjo; Niken Purbasari (Dinasti International Journal of Education Management and Social Science, 2026)
This study examines whether long-term talent commitments within the employment relationship are translated into employee engagement and, through that process, support workplace resilience under uncertainty. A quantitative multi-source survey design was employed across 18 organizations operating in diverse industries. Employees reported sustainable talent management and employee engagement, while supervisors assessed workplace resilience in the focal work context. After screening, 300 usable matched responses were retained and analyzed using partial least squares structural equation modeling with bootstrapping. The findings indicate that sustainable talent management is positively associated with employee engagement, and employee engagement is positively associated with workplace resilience. The indirect effect is also significant, suggesting that long-term organizational commitments are more likely to sustain continuity and cooperative functioning under strain when employees translate them into active involvement in everyday work. These findings show that formal talent arrangements do not become meaningful in the employment relationship simply by being present; they matter when they are experienced as credible, enduring, and enacted commitments. The paper contributes to employee relations research by showing how continuity-oriented organizational commitments gain practical significance through employee engagement. For practice, the findings highlight the importance of visible follow-through on developmental commitments, fair continuity during change, and workplace routines that support employee voice and participation.